Expedient Synthesis of (+)‐Lycopalhine A. (8th January 2016) - Williams, Benjamin M.; Trauner, Dirk
Abstract: Two amino acids play a key role in the first total synthesis of lycopalhine A.l ‐glutamic acid serves as a convenient chiral starting material for the 13‐step synthesis, andl ‐proline promotes an unusual 5‐ endo ‐trig Mannich cyclization that generates the central pyrrolidine ring of the Lycopodium alkaloid. The bicyclo[3.3.0]octanol moiety of the molecule is formed through an intramolecular aldol addition that may occur spontaneously in nature.